2019
DOI: 10.1101/682344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrocytes Contribute to Remote Memory Formation by Modulating Hippocampal-Cortical Communication During Learning

Abstract: 1The consolidation and retrieval of remote memories depend on the coordinated activity of 2 the hippocampus and frontal cortices. However, the exact time at which these regions are 3 recruited to support memory and the interactions between them are still debated. Astrocytes 4 can sense and modify neuronal activity with great precision, but their role in cognitive 5 function has not been extensively explored. To investigate the role of astrocytes in remote 6 memory we expressed the Gi-coupled receptor hM4Di in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…One explanation for this finding is that activation of V1 astrocytes is sufficient to recruit subcortical circuitry, such as thalamocortical circuits, that can underlie brain-wide synchronous events ( Steriade, 2006 ; Crunelli et al, 2018 ). This hypothesis is supported by studies showing subcortical ‘bottom-up’ regulation of slow oscillations ( Steriade et al, 1993 ; Siclari et al, 2014 ; Bernardi et al, 2018 ) and a role of astrocytes in mediating communication between different brain areas ( Kol, 2019 ; Sardinha et al, 2017 ), and could be tested by simultaneously recording from thalamus and cortex during astrocyte activation.…”
Section: Discussionmentioning
confidence: 77%
“…One explanation for this finding is that activation of V1 astrocytes is sufficient to recruit subcortical circuitry, such as thalamocortical circuits, that can underlie brain-wide synchronous events ( Steriade, 2006 ; Crunelli et al, 2018 ). This hypothesis is supported by studies showing subcortical ‘bottom-up’ regulation of slow oscillations ( Steriade et al, 1993 ; Siclari et al, 2014 ; Bernardi et al, 2018 ) and a role of astrocytes in mediating communication between different brain areas ( Kol, 2019 ; Sardinha et al, 2017 ), and could be tested by simultaneously recording from thalamus and cortex during astrocyte activation.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, astrocytes can sense and regulate neuronal activity (Martín et al, 2015;Ma et al, 2016;Stobart et al, 2018;Corkrum et al, 2020). Moreover, manipulating astrocytic activity is sufficient to impact animal behavior and control learning and memory (Suzuki et al, 2011;Adamsky et al, 2018;Kol et al, 2020). It has also been reported that astrocytes in the striatum and in the medial prefrontal cortex can control locomotor behaviors and goal-directed actions by mediating changes in synaptic and neuronal activity (Nagai et al, 2019;Mederos et al, 2020;Corkrum et al, 2020).…”
Section: α2-1-dependent Adult Excitatory Synaptogenesis Controls Effort/reward Evaluationmentioning
confidence: 99%
“…ACC is known to receive VGluT1 inputs from the Claustrum (CLA) and Hippocampus (Chia et al, 2020;Kol et al, 2020;Qadir et al, 2018;White et al, 2018). Moreover, it also receives a plethora of neuromodulatory inputs from the Ventral Tegmental Area (VTA) and the Raphe nuclei (Sun et al, 2019;Elston et al, 2019).…”
Section: Excitation Of Acc-dms Circuit Reduces Effort Exertionmentioning
confidence: 99%
“…Note added in proof: An independent report corroborating the ability of astrocytic signaling to modulate the strength of the CA3‐CA1 synapse and remote, but not recent, memory has recently appeared in bioRxiv (Kol et al, ). In this elegant study, additional mechanistic insights on this topic are examined.…”
mentioning
confidence: 97%